Cover Image, Volume 88, Issue 8. Issue 8 (19th July 2020) - Lensink, Marc F.; Nadzirin, Nurul; Velankar, Sameer; Wodak, Shoshana J.
Abstract : Obverse Cover: The cover image is based on the Original Article* Modeling protein‐protein, protein‐peptide and protein‐oligosaccharide complexes: CAPRI 7th edition by Marc Lensink** et al., https://doi.org/10.1002/prot.25975 .***